INDOOR AIR QUALITY PROGRAMS (Tufts Archival Research Center, 2007)
Confidential; Marginalia; Report detailing indoor air quality programs. Examines strategies, tactics, and the current status of programs within the Tobacco Institute as well as member companies. Discusses the use of labor and the media.